Dielectric relaxation and AC conductivity behaviour of Se80Te15Bi5/PVA nanocomposite film. (October 2019) - Nangia, Rakhi; Shukla, Neeraj K.; Sharma, Ambika; Deepika,
Abstract: An analytical approach has been applied to investigate the dielectric properties and ac conductivity behaviour of a new polymer nanocomposite (PNC) of polyvinyl alcohol (PVA) doped with nanocolloids of Se80 Te15 Bi5 glass over a frequency range of 100 Hz–5 MHz for temperatures ranging from 298 K to 448 K. An increase in dielectric constant and relaxation time for PNC has been seen as compared to pure PVA. The Cole-Cole model of relaxation shows good agreement with experimental data. The ac conductivity (σac ) behaviour has been found to follow the Jonscher's power law Aω s . Prevailing mechanism of conduction has been confirmed to be correlated barrier hopping (CBH) type. The synthesized PNC has been used as an active layer in the fabrication of a memory device. Electrical characterization of the device has been done by current-voltage (I–V) and capacitance-voltage (C–V) measurements. The switching between high conductive (ON) and low conductive (OFF) states of the device may be attributed to charge trapping and de-trapping in Se80 Te15 Bi5 nanocolloids. The retention characteristic of the device, determined by capacitance-time (C-t) measurements indicates its good reliability and stability. Highlights: New nanocomposite films Se80 Te15 Bi5 /PVA PNC have been prepared by chemical precipitation method. Significant increase in permittivity and dielectric relaxation time of PNC is observed as compared to pure PVA. The dielectric response and relaxation mechanism follows Cole-Cole model and deviates from ideal Debye response. The switching behaviour of the fabricated device is due to charge trapping and de-trapping in Se80 Te15 Bi5 nanoparticles. The results suggest wide range of applications of PNCs in memory devices.